Building glass ceramic gel heat insulation film
By using nano -ceramic materials dispersible slurry, composite ultraviolet absorbers, modified Ello stone powder, and PET mother grains, building glass ceramic gel insulation film, solving the existing insufficient anti -ultraviolet and antibacterial properties The problem realizes higher thermal insulation and better durability and environmental protection performance.
Patent Information
- Application Number
- CN202411660724.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing glass thermal insulation film has shortcomings in its ultraviolet resistance and antibacterial properties, and it is difficult to meet the actual use needs.
The building glass ceramic gel insulation film composed of nano -ceramic materials disperse, composite ultraviolet absorbers, modified Elot stone powder, and PET mother grains. The nano -ceramic materials are prepared through the superbody -to -loving filling grid technology, and the aluminate puppets are modified by aluminate puppets to improve the mechanical strength and toughness.
It significantly improves the thermal insulation performance, anti -ultraviolet performance and antibacterial performance of the thermal insulation film, enhance the durability and anti -aging performance of the material, and reduce the pollution of the environment, and meet the requirements of environmental protection and sustainable development.
Smart Images

Figure BDA0005143272290000121 
Figure BDA0005143272290000131 
Figure BDA0005143272290000132
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal insulation films, and in particular to a building glass ceramic gel thermal insulation film. Background Art
[0002] With the continuous advancement of modern construction technology, the functionality and performance requirements of building materials are also increasing, especially glass materials. As the main transparent material in buildings, they not only need to have good light transmittance and aesthetics, but also need to have excellent heat insulation, sun protection and other properties to adapt to the climatic conditions and building use requirements of different regions. Moreover, architectural glass is the key to affecting air conditioning energy consumption.
[0003] Although traditional glass insulation materials, such as coated glass and hollow glass, have improved the thermal insulation performance of glass to a certain extent, their production costs are high and the process is complex. In addition, their performance stability in certain special environments, such as extremely high or low temperatures, needs to be improved.
[0004] For example, the invention of Chinese Patent No. 202210647003.9 discloses a reflective nano-ceramic thermal insulation film and its film-making process. The invention uses silicone resin, titanium dioxide powder, ultraviolet absorber, ceramic powder, etc. as raw materials for mixed reaction. The selected titanium dioxide has a higher refractive index, which improves the light scattering ability of the nano-ceramic thermal insulation film, improves the transparency and thermal insulation of the coating, and 2-hydroxy-4-n-octyloxybenzophenone and 2'-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole are used as ultraviolet absorbers to achieve the purpose of blocking ultraviolet rays. The nano-ceramic powder has a nano-scale size and has the advantages of good chemical stability and strong heat resistance. However, the thermal insulation film prepared by this invention still needs further improvement in terms of anti-ultraviolet performance and antibacterial performance. Therefore, how to design a glass thermal insulation material to improve the anti-ultraviolet performance and antibacterial performance of the existing thermal insulation film has become a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention
[0005] Technical issues solved
[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a building glass ceramic gel insulation film, which can effectively solve the problem that the thermal insulation performance and anti-ultraviolet performance of the glass insulation film in the prior art cannot meet the actual use requirements.
[0007] Technical Solution
[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0009] A building glass ceramic gel thermal insulation film, the building glass ceramic gel thermal insulation film is composed of the following components: nano ceramic material dispersion slurry, composite ultraviolet absorber component, modified halloysite powder and PET masterbatch;
[0010] The nano ceramic material dispersion slurry is first prepared into ultrafine particle powder by ball milling and calcining with alumina nano powder, yttrium oxalate and zirconium carbonate as raw materials, and then the ultrafine particle powder and modified nano titanium dioxide are prepared into nano ceramic material dispersion slurry by a high gravity rotating packed bed;
[0011] The composite ultraviolet absorber component is prepared by mixing a plurality of ultraviolet absorbers;
[0012] The modified halloysite powder is prepared by modifying the halloysite powder with an aluminate coupling agent.
[0013] Furthermore, the preparation method of the aluminum oxide nanopowder is:
[0014] Ammonium aluminum sulfate is placed in a box furnace and heated to 600°C at a heating rate of 3°C / min, kept warm for 2 hours, and then cooled to room temperature. Then, the temperature is increased to 1200°C at a heating rate of 5°C / min, kept warm for 1 hour, and then cooled to room temperature. After ball milling with anhydrous ethanol for 24 hours, it is placed in an oven at 60°C and dried to constant weight to obtain aluminum oxide nanopowder.
[0015] Furthermore, the preparation steps of the ultrafine particle powder are:
[0016] Step 1, weighing a calculated amount of yttrium oxalate and zirconium carbonate in a molar ratio of 3:97 and mixing them, then adding a calculated amount of oxalic acid in a molar ratio of metal ions to oxalic acid of 2:3, and then adding aluminum oxide nanopowder with a weight of 1 / 3 of the zirconium carbonate, the result is recorded as a mixed component, and acetic acid and anhydrous ethanol are mixed in an equal volume ratio and recorded as a promoting mixed solution;
[0017] Step 2: Add the mixed components, zirconium beads and the mixed liquid into the ball mill according to the material-ball-liquid ratio of 1:10:1, ball mill at a ball milling speed of 100-300 r / min for 1-4 hours, and then place it in a blast drying oven at a temperature of 110°C for 3 hours, then place it in a ball mill for ball milling, and then place it in a muffle furnace for calcination. After ball milling again, the ultrafine particle powder is obtained.
[0018] Furthermore, the specific operation of ball milling in step 2 is ball milling at a ball milling speed of 200 r / min for 2 hours, and the specific operation of calcination in step 2 is calcination at a temperature of 650° C. for 2-3 hours.
[0019] Furthermore, the preparation method of the modified nano titanium dioxide is:
[0020] 8-10g of nano titanium dioxide is weighed and dispersed in 200mL of anhydrous ethanol. After stirring at a stirring speed of 500r / min for 10min, 2-3g of hexadecyltrimethylammonium bromide, 1-2g of dodecyltrimethylammonium chloride, 1-2g of tetradecyldimethylbenzylammonium chloride, 1-2g of dioctyldimethylammonium chloride and 2-3g of ditetradecyldimethylammonium chloride are added. After ultrasonic dispersion at a frequency of 28kHz for 30min, 10-12g of silane coupling agent KH-560 is added. After stirring at a stirring speed of 500r / min for 30min at a water bath temperature of 90°C, the mixture is placed in a blast drying oven at 85°C and dried to constant weight. The modified nano titanium dioxide is obtained after grinding through a 200-mesh sieve.
[0021] Furthermore, the preparation steps of the nano-ceramic material dispersion slurry are:
[0022] 7-8g of ultrafine particle powder, 2-3g of modified nano titanium dioxide and 40g of ethyl acetate are poured into the packing layer of the supergravity rotating packed bed. At a temperature of 50-60°C and a rotation speed of 500-2500r / min, the rotor provides strong supergravity for the molecular mixing process. Then, the mixed precipitate is thrown out from the packing layer into the cavity between the rotor and the inner wall, and then discharged from the discharge port and collected to obtain a nano-ceramic material dispersion slurry.
[0023] Furthermore, the preparation method of the composite ultraviolet absorber is:
[0024] Hexamethylphosphoric triamide, 2-hydroxy-4-octyloxybenzophenone, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and monobenzoic acid resorcinol ester were weighed in equal weight ratios and poured into a ball mill for 30 minutes at a speed of 500 r / min to obtain a composite ultraviolet absorber.
[0025] Furthermore, the preparation method of the modified halloysite powder is:
[0026] The halloysite powder is placed in a vacuum drying oven at 80°C and dried for 12 hours, then 8-10 g is weighed and placed in a flask, stirred at 100-110°C at a stirring speed of 300 r / min for 5 minutes, and then 0.5-0.6 g of aluminate coupling agent distearoyloxyisopropoxyaluminate is added, and stirring is continued at the original stirring speed for 30 minutes to obtain the modified halloysite powder.
[0027] Furthermore, the preparation method of the architectural glass ceramic gel insulation film is:
[0028] S1, weighing 95-100 parts by weight of PET masterbatch, 3-4 parts by weight of nano-ceramic material dispersion slurry, 1-2 parts by weight of composite UV absorber component and 0.5-0.6 parts by weight of modified halloysite powder, melt-blending them, and then extruding and granulating them through a twin-screw extruder to obtain a PET functional masterbatch;
[0029] S2. Biaxially stretching the PET functional masterbatch into a film to obtain a building glass ceramic gel thermal insulation film.
[0030] Furthermore, the process parameters of the biaxial stretching in S2 include: a temperature of 105-115° C., a stretching rate of 90-120 mm / s, and a transverse and longitudinal stretching ratio of 3-4.
[0031] Beneficial Effects
[0032] The present invention provides a building glass ceramic gel thermal insulation film. Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The present invention combines alumina nanopowder, yttrium oxalate, zirconium carbonate and modified nano-titanium dioxide, and prepares a nano-ceramic material dispersion slurry through a supergravity rotating packed bed. Since the nano-ceramic material has high thermal resistance and low thermal conductivity, it can form a thermal barrier in the material to reduce heat transfer. Therefore, introducing the nano-ceramic material dispersion slurry into the thermal insulation film can significantly reduce the heat conduction efficiency and effectively improve the thermal insulation performance of the material; wherein, yttrium oxalate and zirconium carbonate are the main components of the ultrafine particle powder, which are mixed in a specific molar ratio and combined with alumina nanopowder to further enhance the performance of the material. The introduction of yttrium oxalate can improve the thermal stability and antioxidant properties of the material, while zirconium carbonate can enhance the hardness and wear resistance of the material. The mutual cooperation of the two components can make the ceramic gel thermal insulation film have better durability and anti-aging performance while maintaining high thermal insulation performance;
[0034] Secondly, as another key component, modified nano titanium dioxide can improve its dispersibility and stability in nano-ceramic material dispersion slurry through specific surface modification technology. The modified nano titanium dioxide not only has excellent ultraviolet absorption and photocatalytic properties, but can also form ionic bonds with alumina nanopowder and zirconium carbonate through electrostatic action, and form coordination bonds with yttrium oxalate through coordination. Through the above-mentioned tight chemical bonding, the overall performance of the material can be further enhanced. This chemical bonding enables the ceramic gel insulation film to better maintain its structural stability and performance integrity when subjected to external forces or high temperature environments.
[0035] 2. In the present invention, by dispersing different types of antibacterial agents with nano titanium dioxide, part of the antibacterial agents can be adsorbed and dispersed in the pore structure on the surface of the nano titanium dioxide, and then the modified nano titanium dioxide with the antibacterial agent loaded on the surface can be more evenly dispersed in the PET material through the modification of the silane coupling agent, thereby enhancing the weather resistance and heat insulation of the thermal insulation film through the effect of the modified nano titanium dioxide, and further enhancing the optical stability and antibacterial property of the thermal insulation film; different types of antibacterial agents added in the modification process of the modified nano titanium dioxide have different antibacterial mechanisms, such as hexadecyltrimethylammonium bromide, tetradecyldimethylbenzyl Ammonium chloride, dodecyltrimethylammonium chloride and dioctyldimethylammonium chloride can change the permeability of bacterial cells, allowing chlorine, phosphorus and other substances in the bacteria to escape, leading to bacterial autolysis. Ditetradecyldimethylammonium chloride can bind to proteins in bacterial cells, causing changes in the spatial structure of the proteins and causing them to lose their original biological activity. Different antimicrobial agents can work together on the microbial cell wall, cell membrane or cell interior to achieve synergistic killing or inhibition of microorganisms. These antimicrobial agents can exert their antibacterial effects by destroying the cell structure of microorganisms, interfering with their metabolic processes or inhibiting their growth and reproduction.
[0036] 3. The present invention can effectively absorb and convert ultraviolet energy by mixing a variety of ultraviolet absorbers, reduce the impact of ultraviolet rays on the indoor environment and human health, and protect the film material and the building glass itself from damage by ultraviolet rays. By compounding different types of ultraviolet absorbers, it can absorb ultraviolet rays of different bands and convert them into harmless heat energy or low-energy radiation, thereby achieving better anti-ultraviolet performance and improving the durability of the thermal insulation film to a certain extent; among them, 2-hydroxy-4-n-octyloxybenzophenone mainly absorbs ultraviolet rays with a wavelength of 240-340nm, and 2-(2ˊ-hydroxy-5ˊ-methylphenyl)benzotriazole can absorb ultraviolet rays with a wavelength of 270-380nm. The synergistic cooperation between different ultraviolet absorbers can expand the range of ultraviolet absorption bands, thereby further enhancing the anti-ultraviolet performance of the thermal insulation film.
[0037] 4. The halloysite powder in the present invention is modified with an aluminate coupling agent and then blended with a PET masterbatch, which can enhance the interfacial bonding force between the halloysite powder and the PET masterbatch, thereby improving the mechanical strength and toughness of the thermal insulation film. Moreover, the PET masterbatch has good melt fluidity and plasticity, which is convenient for melt blending with other components. The biaxial stretching technology can further improve the uniformity and strength of the material, so that the thermal insulation film prepared therefrom has better application performance.
[0038] 5. The raw materials used in the present invention, such as alumina nanopowder and halloysite powder, are all natural or recyclable materials, which reduce the pollution to the environment during the preparation process and meet the requirements of environmental protection and sustainable development. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] The present invention will be further described below in conjunction with the embodiments.
[0041] Example 1
[0042] A building glass ceramic gel thermal insulation film of this embodiment, the building glass ceramic gel thermal insulation film is composed of the following components: nano ceramic material dispersion slurry, composite ultraviolet absorber component, modified halloysite powder and PET masterbatch;
[0043] The nano ceramic material dispersion slurry is firstly prepared into ultrafine particle powder by ball milling and calcining with alumina nano powder, yttrium oxalate and zirconium carbonate as raw materials, and then the ultrafine particle powder and modified nano titanium dioxide are prepared into nano ceramic material dispersion slurry by ultra-gravity rotating packed bed;
[0044] The composite ultraviolet absorber component is prepared by mixing a plurality of ultraviolet absorbers;
[0045] The modified halloysite powder is prepared by modifying the halloysite powder with an aluminate coupling agent.
[0046] The preparation method of alumina nanopowder is:
[0047] Ammonium aluminum sulfate is placed in a box furnace and heated to 600°C at a heating rate of 3°C / min, kept warm for 2 hours, and then cooled to room temperature. Then, the temperature is increased to 1200°C at a heating rate of 5°C / min, kept warm for 1 hour, and then cooled to room temperature. After ball milling with anhydrous ethanol for 24 hours, it is placed in an oven at 60°C and dried to constant weight to obtain aluminum oxide nanopowder.
[0048] The preparation steps of ultrafine particle powder are as follows:
[0049] Step 1, weighing a calculated amount of yttrium oxalate and zirconium carbonate in a molar ratio of 3:97 and mixing them, then adding a calculated amount of oxalic acid in a molar ratio of metal ions to oxalic acid of 2:3, and then adding aluminum oxide nanopowder with a weight of 1 / 3 of the zirconium carbonate, the result is recorded as a mixed component, and acetic acid and anhydrous ethanol are mixed in an equal volume ratio and recorded as a promoting mixed solution;
[0050] Step 2: Add the mixed components, zirconium beads and the mixed liquid into the ball mill according to the material-ball-liquid ratio of 1:10:1, ball mill at a ball milling speed of 100 r / min for 1 hour, place in a blast drying oven at a temperature of 110°C for 3 hours, then place in a ball mill at a ball milling speed of 200 r / min for 2 hours, place in a muffle furnace for calcination at a temperature of 650°C for 2 hours, and ball mill again to obtain an ultrafine particle powder.
[0051] Preparation method of modified nano titanium dioxide:
[0052] 8 g of nano titanium dioxide was weighed and dispersed in 200 mL of anhydrous ethanol. After stirring at a stirring speed of 500 r / min for 10 min, 2 g of hexadecyltrimethylammonium bromide, 1 g of dodecyltrimethylammonium chloride, 1 g of tetradecyldimethylbenzylammonium chloride, 1 g of dioctyldimethylammonium chloride and 2 g of ditetradecyldimethylammonium chloride were added. After ultrasonic dispersion at a frequency of 28 kHz for 30 min, 10 g of silane coupling agent KH-560 was added. After stirring at a stirring speed of 500 r / min for 30 min at a water bath temperature of 90 ° C, the mixture was placed in a blast drying oven at 85 ° C and dried to constant weight. The modified nano titanium dioxide was obtained after grinding through a 200 mesh sieve.
[0053] The preparation steps of nano-ceramic material dispersion slurry are as follows:
[0054] 7g of ultrafine particle powder, 2g of modified nano titanium dioxide and 40g of ethyl acetate are poured into the packing layer of the supergravity rotating packed bed. At a temperature of 50°C and a rotation speed of 500r / min, the rotor provides strong supergravity for the molecular mixing process. Then, the mixed precipitate is thrown out from the packing layer into the cavity between the rotor and the inner wall, and then discharged from the discharge port and collected to obtain a nano-ceramic material dispersion slurry.
[0055] The preparation method of the composite ultraviolet absorber is:
[0056] Hexamethylphosphoric triamide, 2-hydroxy-4-octyloxybenzophenone, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and monobenzoic acid resorcinol ester were weighed in equal weight ratios and poured into a ball mill for 30 minutes at a speed of 500 r / min to obtain a composite ultraviolet absorber.
[0057] The preparation method of modified halloysite powder is:
[0058] The halloysite powder was placed in a vacuum drying oven at 80°C and dried for 12 hours. Then 8 g was weighed and placed in a flask. After stirring at 100°C and 300 r / min for 5 minutes, 0.5 g of aluminate coupling agent distearoyloxyisopropoxyaluminate was added. The mixture was stirred at the original stirring speed for 30 minutes to obtain the modified halloysite powder.
[0059] The preparation method of building glass ceramic gel insulation film is as follows:
[0060] S1, weighing 95 parts by weight of PET masterbatch, 3 parts by weight of nano-ceramic material dispersion slurry, 1 part by weight of composite UV absorber component and 0.5 parts by weight of modified halloysite powder, melt-blending them, and then extruding and granulating them through a twin-screw extruder to obtain a PET functional masterbatch;
[0061] S2. Biaxially stretching the PET functional masterbatch into a film to obtain a building glass ceramic gel thermal insulation film, wherein the biaxial stretching temperature is 105° C., the biaxial stretching rate is 90 mm / s, and the transverse and longitudinal stretching ratios of the biaxial stretching are 3.
[0062] Example 2
[0063] A building glass ceramic gel thermal insulation film of this embodiment, the building glass ceramic gel thermal insulation film is composed of the following components: nano ceramic material dispersion slurry, composite ultraviolet absorber component, modified halloysite powder and PET masterbatch;
[0064] The nano ceramic material dispersion slurry is firstly prepared into ultrafine particle powder by ball milling and calcining with alumina nano powder, yttrium oxalate and zirconium carbonate as raw materials, and then the ultrafine particle powder and modified nano titanium dioxide are prepared into nano ceramic material dispersion slurry by ultra-gravity rotating packed bed;
[0065] The composite ultraviolet absorber component is prepared by mixing a plurality of ultraviolet absorbers;
[0066] The modified halloysite powder is prepared by modifying the halloysite powder with an aluminate coupling agent.
[0067] The preparation method of alumina nanopowder is:
[0068] Ammonium aluminum sulfate is placed in a box furnace and heated to 600°C at a heating rate of 3°C / min, kept warm for 2 hours, and then cooled to room temperature. Then, the temperature is increased to 1200°C at a heating rate of 5°C / min, kept warm for 1 hour, and then cooled to room temperature. After ball milling with anhydrous ethanol for 24 hours, it is placed in an oven at 60°C and dried to constant weight to obtain aluminum oxide nanopowder.
[0069] The preparation steps of ultrafine particle powder are as follows:
[0070] Step 1, weighing a calculated amount of yttrium oxalate and zirconium carbonate in a molar ratio of 3:97 and mixing them, then adding a calculated amount of oxalic acid in a molar ratio of metal ions to oxalic acid of 2:3, and then adding aluminum oxide nanopowder with a weight of 1 / 3 of the zirconium carbonate, the result is recorded as a mixed component, and acetic acid and anhydrous ethanol are mixed in an equal volume ratio and recorded as a promoting mixed solution;
[0071] Step 2: Add the mixed components, zirconium beads and the mixed liquid into the ball mill according to the material-ball-liquid ratio of 1:10:1, ball mill at a ball milling speed of 300 r / min for 4 hours, place in a blast drying oven at a temperature of 110°C for 3 hours, then place in a ball mill at a ball milling speed of 200 r / min for 2 hours, place in a muffle furnace for calcination at a temperature of 650°C for 3 hours, and ball mill again to obtain an ultrafine particle powder.
[0072] Preparation method of modified nano titanium dioxide:
[0073] Weigh 10g of nano titanium dioxide and disperse it in 200mL of anhydrous ethanol. Stir at a stirring speed of 500r / min for 10min, then add 3g of hexadecyltrimethylammonium bromide, 2g of dodecyltrimethylammonium chloride, 2g of tetradecyldimethylbenzylammonium chloride, 2g of dioctyldimethylammonium chloride and 3g of ditetradecyldimethylammonium chloride. Ultrasonic dispersion is carried out at a frequency of 28kHz for 30min, then 12g of silane coupling agent KH-560 is added. Stir at a stirring speed of 500r / min for 30min at a water bath temperature of 90°C, place in a blast drying oven at 85°C and dry to constant weight. The modified nano titanium dioxide is obtained after grinding through a 200-mesh sieve.
[0074] The preparation steps of nano-ceramic material dispersion slurry are as follows:
[0075] 8g of ultrafine particle powder, 3g of modified nano titanium dioxide and 40g of ethyl acetate are poured into the packing layer of the supergravity rotating packed bed. At a temperature of 60°C and a rotation speed of 2500r / min, the rotor provides strong supergravity for the molecular mixing process. Then, the mixed precipitate is thrown out from the packing layer into the cavity between the rotor and the inner wall, and then discharged from the discharge port and collected to obtain a nano-ceramic material dispersion slurry.
[0076] The preparation method of the composite ultraviolet absorber is:
[0077] Hexamethylphosphoric triamide, 2-hydroxy-4-octyloxybenzophenone, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and monobenzoic acid resorcinol ester were weighed in equal weight ratios and poured into a ball mill for 30 minutes at a speed of 500 r / min to obtain a composite ultraviolet absorber.
[0078] The preparation method of modified halloysite powder is:
[0079] The halloysite powder was placed in a vacuum drying oven at 80°C and dried for 12 hours. Then 10 g was weighed and placed in a flask. After stirring at 110°C and a stirring speed of 300 r / min for 5 minutes, 0.6 g of aluminate coupling agent distearoyloxyisopropoxyaluminate was added. The mixture was stirred at the original stirring speed for 30 minutes to obtain the modified halloysite powder.
[0080] The preparation method of building glass ceramic gel insulation film is as follows:
[0081] S1, weighing 100 parts by weight of PET masterbatch, 4 parts by weight of nano-ceramic material dispersion slurry, 2 parts by weight of composite UV absorber component and 0.6 parts by weight of modified halloysite powder, melt-blending them, and then extruding and granulating them through a twin-screw extruder to obtain a PET functional masterbatch;
[0082] S2. Biaxially stretching the PET functional masterbatch into a film to obtain a building glass ceramic gel thermal insulation film, wherein the biaxial stretching temperature is 115° C., the biaxial stretching rate is 120 mm / s, and the transverse and longitudinal stretching ratios of the biaxial stretching are 4.
[0083] Example 3
[0084] A building glass ceramic gel thermal insulation film of this embodiment, the building glass ceramic gel thermal insulation film is composed of the following components: nano ceramic material dispersion slurry, composite ultraviolet absorber component, modified halloysite powder and PET masterbatch;
[0085] The nano ceramic material dispersion slurry is firstly prepared into ultrafine particle powder by ball milling and calcining with alumina nano powder, yttrium oxalate and zirconium carbonate as raw materials, and then the ultrafine particle powder and modified nano titanium dioxide are prepared into nano ceramic material dispersion slurry by ultra-gravity rotating packed bed;
[0086] The composite ultraviolet absorber component is prepared by mixing a plurality of ultraviolet absorbers;
[0087] The modified halloysite powder is prepared by modifying the halloysite powder with an aluminate coupling agent.
[0088] The preparation method of alumina nanopowder is:
[0089] Ammonium aluminum sulfate is placed in a box furnace and heated to 600°C at a heating rate of 3°C / min, kept warm for 2 hours, and then cooled to room temperature. Then, the temperature is increased to 1200°C at a heating rate of 5°C / min, kept warm for 1 hour, and then cooled to room temperature. After ball milling with anhydrous ethanol for 24 hours, it is placed in an oven at 60°C and dried to constant weight to obtain aluminum oxide nanopowder.
[0090] The preparation steps of ultrafine particle powder are as follows:
[0091] Step 1, weighing a calculated amount of yttrium oxalate and zirconium carbonate in a molar ratio of 3:97 and mixing them, then adding a calculated amount of oxalic acid in a molar ratio of metal ions to oxalic acid of 2:3, and then adding aluminum oxide nanopowder with a weight of 1 / 3 of the zirconium carbonate, the result is recorded as a mixed component, and acetic acid and anhydrous ethanol are mixed in an equal volume ratio and recorded as a promoting mixed solution;
[0092] Step 2: Add the mixed components, zirconium beads and the mixed liquid into the ball mill at a material-ball-liquid ratio of 1:10:1, ball mill at a ball milling speed of 200 r / min for 3 hours, place in a blast drying oven at a temperature of 110°C for 3 hours, then place in a ball mill at a ball milling speed of 200 r / min for 2 hours, place in a muffle furnace for calcination at a temperature of 650°C for 3 hours, and ball mill again to obtain an ultrafine particle powder.
[0093] Preparation method of modified nano titanium dioxide:
[0094] 9 g of nano titanium dioxide was weighed and dispersed in 200 mL of anhydrous ethanol. After stirring at a stirring speed of 500 r / min for 10 min, 3 g of hexadecyltrimethylammonium bromide, 2 g of dodecyltrimethylammonium chloride, 1 g of tetradecyldimethylbenzylammonium chloride, 2 g of dioctyldimethylammonium chloride and 2 g of ditetradecyldimethylammonium chloride were added. After ultrasonic dispersion at a frequency of 28 kHz for 30 min, 11 g of silane coupling agent KH-560 was added. After stirring at a stirring speed of 500 r / min for 30 min at a water bath temperature of 90 ° C, the mixture was placed in a blast drying oven at 85 ° C and dried to constant weight. The modified nano titanium dioxide was obtained after grinding through a 200 mesh sieve.
[0095] The preparation steps of nano-ceramic material dispersion slurry are as follows:
[0096] 8g of ultrafine particle powder, 2g of modified nano titanium dioxide and 40g of ethyl acetate are poured into the packing layer of the supergravity rotating packed bed. At a temperature of 55°C and a rotation speed of 1500r / min, the rotor provides strong supergravity for the molecular mixing process. Then, the mixed precipitate is thrown out from the packing layer into the cavity between the rotor and the inner wall, and then discharged from the discharge port and collected to obtain a nano-ceramic material dispersion slurry.
[0097] The preparation method of the composite ultraviolet absorber is:
[0098] Hexamethylphosphoric triamide, 2-hydroxy-4-octyloxybenzophenone, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and monobenzoic acid resorcinol ester were weighed in equal weight ratios and poured into a ball mill for 30 minutes at a speed of 500 r / min to obtain a composite ultraviolet absorber.
[0099] The preparation method of modified halloysite powder is:
[0100] The halloysite powder was placed in a vacuum drying oven at 80°C and dried for 12 hours. Then 9 g was weighed and placed in a flask. After stirring at 105°C and 300 r / min for 5 minutes, 0.5 g of aluminate coupling agent distearoyloxyisopropoxyaluminate was added. The mixture was stirred at the original stirring speed for 30 minutes to obtain the modified halloysite powder.
[0101] The preparation method of building glass ceramic gel insulation film is as follows:
[0102] S1, weighing 98 parts by weight of PET masterbatch, 4 parts by weight of nano-ceramic material dispersion slurry, 2 parts by weight of composite UV absorber component and 0.6 parts by weight of modified halloysite powder, melt-blending them, and then extruding and granulating them through a twin-screw extruder to obtain a PET functional masterbatch;
[0103] S2. Biaxially stretching the PET functional masterbatch into a film to obtain a building glass ceramic gel thermal insulation film, wherein the biaxial stretching temperature is 110° C., the biaxial stretching rate is 105 mm / s, and the transverse and longitudinal stretching ratios of the biaxial stretching are 4.
[0104] Comparative Example 1
[0105] The architectural glass ceramic gel thermal insulation film provided in this comparative example is substantially the same as that in Example 1, the main difference is that the ultrafine particle powder in Example 1 is replaced by aluminum oxide nanopowder in this comparative example 1.
[0106] Comparative Example 2
[0107] The architectural glass ceramic gel thermal insulation film provided in this comparative example is substantially the same as that in Example 1, the main difference is that the modified nano titanium dioxide in Example 1 is replaced by unmodified nano titanium dioxide in this comparative example 2.
[0108] Comparative Example 3
[0109] The architectural glass ceramic gel thermal insulation film provided in this comparative example is substantially the same as that in Example 1, the main difference is that the modified halloysite powder in Example 1 is replaced by unmodified halloysite powder in this comparative example 3.
[0110] Performance Testing
[0111] The architectural glass ceramic gel thermal insulation films prepared in Examples 1-3 and Comparative Examples 1-3 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, respectively. Then, the performance of Examples 1-3 and Comparative Examples 1-3 is tested. The specific testing methods and test items are as follows:
[0112] 1. The tensile properties of Examples 1-3 and Comparative Examples 1-3 were tested according to the standard of GB / T1040-1992, and the obtained tensile strength and elongation at break data are recorded in Table 1;
[0113] 2. The impact properties of Examples 1-3 and Comparative Examples 1-3 were tested according to the standard of GB / T1043-1993, and the obtained impact strength data are recorded in Table 1;
[0114] 3. The antibacterial properties of Examples 1-3 and Comparative Examples 1-3 were tested according to the standard of GB / T31402-2015, and the obtained comprehensive antibacterial rate data are recorded in Table 1;
[0115] 4. The samples in Examples 1-3 and Comparative Examples 1-3 were placed under a 30W UV lamp at a distance of 10 cm, and the aging marks of the samples after irradiation for 12 h, 24 h and 48 h were recorded. The obtained data are recorded in Table 2;
[0116] 5. The samples in Examples 1-3 and Comparative Examples 1-3 were attached to the side wall of the glass, and the glass was heated for 1 hour with a 275W infrared lamp. The temperature difference between the two sides of the glass was recorded, and the obtained data were recorded in Table 2;
[0117] Table 1
[0118]
[0119]
[0120] Table 2
[0121]
[0122] It can be seen from the data in Table 1 and Table 2 that the architectural glass ceramic gel insulation film prepared in Examples 1-3 has better mechanical properties than that of Comparative Example 1, indicating that the ultrafine particle powder added in the preparation process of the insulation film can better improve the mechanical properties than the aluminum oxide nanopowder, because the ultrafine particle powder contains yttrium oxalate and zirconium carbonate, and yttrium oxalate and zirconium carbonate can be combined with aluminum oxide nanopowder after mixing in a specific molar ratio, thereby further enhancing the performance of the material. The introduction of yttrium oxalate can improve the thermal stability and antioxidant properties of the material, while zirconium carbonate can enhance the hardness and wear resistance of the material. The synergistic effect of these two components enables the ceramic gel insulation film to maintain high thermal insulation performance while also having better durability and anti-aging properties.
[0123] The architectural glass ceramic gel thermal insulation film prepared in Examples 1-3 has better antibacterial and thermal insulation properties than Comparative Examples 2-3. The nano titanium dioxide in Comparative Example 2 has not been antibacterial modified, and the halloysite powder in Comparative Example 3 has not been surface modified, indicating that adding modified nano titanium dioxide and modified halloysite powder in the preparation of thermal insulation film can significantly enhance the antibacterial and thermal insulation properties. Therefore, the architectural glass ceramic gel thermal insulation film prepared by the present invention has an excellent market application prospect.
[0124] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0125] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A building glass ceramic gel thermal insulation film, characterized in that: The architectural glass ceramic gel thermal insulation film is composed of the following components: 3-4 parts by weight of nano-ceramic material dispersion slurry, 1-2 parts by weight of composite ultraviolet absorber component, 0.5-0.6 parts by weight of modified halloysite powder and 95-100 parts by weight of PET masterbatch; The nano ceramic material dispersion slurry is first prepared into ultrafine particle powder by ball milling and calcining with aluminum oxide nano powder, yttrium oxalate and zirconium carbonate as raw materials, and then the ultrafine particle powder and modified nano titanium dioxide are prepared into nano ceramic material dispersion slurry by using a high gravity rotating packed bed; The composite ultraviolet absorber component is prepared by mixing four ultraviolet absorbers; The modified halloysite powder is prepared by modifying the halloysite powder with an aluminate coupling agent.
2. The architectural glass ceramic gel thermal insulation film according to claim 1, characterized in that: The preparation method of the aluminum oxide nanopowder is: Ammonium aluminum sulfate is placed in a box furnace and heated to 600°C at a heating rate of 3°C / min, kept warm for 2 hours, and then cooled to room temperature. Then, the temperature is increased to 1200°C at a heating rate of 5°C / min, kept warm for 1 hour, and then cooled to room temperature. After ball milling with anhydrous ethanol for 24 hours, it is placed in an oven at 60°C and dried to constant weight to obtain aluminum oxide nanopowder.
3. The architectural glass ceramic gel thermal insulation film according to claim 1, characterized in that: The preparation steps of the ultrafine particle powder are: Step 1, weighing a calculated amount of yttrium oxalate and zirconium carbonate in a molar ratio of 3:97 and mixing them, then adding a calculated amount of oxalic acid in a molar ratio of metal ions to oxalic acid of 2:3, and then adding aluminum oxide nanopowder with a weight of 1 / 3 of the zirconium carbonate, the result is recorded as a mixed component, and acetic acid and anhydrous ethanol are mixed in an equal volume ratio and recorded as a promoting mixed solution; Step 2: Add the mixed components, zirconium beads and the mixed liquid into the ball mill according to the material-ball-liquid ratio of 1:10:1, ball mill at a ball milling speed of 100-300 r / min for 1-4 hours, and then place it in a blast drying oven at a temperature of 110°C for 3 hours, then place it in a ball mill for ball milling, and then place it in a muffle furnace for calcination. After ball milling again, the ultrafine particle powder is obtained.
4. The architectural glass ceramic gel thermal insulation film according to claim 3, characterized in that: The specific operation of ball milling in step 2 is ball milling at a ball milling speed of 200 r / min for 2 hours, and the specific operation of calcination in step 2 is calcination at a temperature of 650° C. for 2-3 hours.
5. The architectural glass ceramic gel thermal insulation film according to claim 1, characterized in that: The preparation method of the modified nano titanium dioxide: 8-10g of nano titanium dioxide is weighed and dispersed in 200mL of anhydrous ethanol. After stirring at a stirring speed of 500r / min for 10min, 2-3g of hexadecyltrimethylammonium bromide, 1-2g of dodecyltrimethylammonium chloride, 1-2g of tetradecyldimethylbenzylammonium chloride, 1-2g of dioctyldimethylammonium chloride and 2-3g of ditetradecyldimethylammonium chloride are added. After ultrasonic dispersion at a frequency of 28kHz for 30min, 10-12g of silane coupling agent KH-560 is added. After stirring at a stirring speed of 500r / min for 30min at a water bath temperature of 90°C, the mixture is placed in a blast drying oven at 85°C and dried to constant weight. The modified nano titanium dioxide is obtained after grinding through a 200-mesh sieve.
6. The architectural glass ceramic gel thermal insulation film according to claim 1, characterized in that: The preparation steps of the nano-ceramic material dispersion slurry are: 7-8g of ultrafine particle powder, 2-3g of modified nano titanium dioxide and 40g of ethyl acetate are poured into the packing layer of the supergravity rotating packed bed. At a temperature of 50-60°C and a rotation speed of 500-2500r / min, the rotor provides strong supergravity for the molecular mixing process. Then, the mixed precipitate is thrown out from the packing layer into the cavity between the rotor and the inner wall, and then discharged from the discharge port and collected to obtain a nano-ceramic material dispersion slurry.
7. The architectural glass ceramic gel thermal insulation film according to claim 1, characterized in that: The preparation method of the composite ultraviolet absorber is: Hexamethylphosphoric triamide, 2-hydroxy-4-octyloxybenzophenone, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and monobenzoic acid resorcinol ester were weighed in equal weight ratios and poured into a ball mill for 30 minutes at a speed of 500 r / min to obtain a composite ultraviolet absorber.
8. The architectural glass ceramic gel thermal insulation film according to claim 1, characterized in that: The preparation method of the modified halloysite powder is: The halloysite powder is placed in a vacuum drying oven at 80°C and dried for 12 hours, then 8-10 g is weighed and placed in a flask, stirred at 100-110°C at a stirring speed of 300 r / min for 5 minutes, and then 0.5-0.6 g of aluminate coupling agent distearoyloxyisopropoxyaluminate is added, and stirring is continued at the original stirring speed for 30 minutes to obtain the modified halloysite powder.
9. The architectural glass ceramic gel thermal insulation film according to claim 1, characterized in that: The preparation method of the architectural glass ceramic gel thermal insulation film is as follows: S1, weighing PET masterbatch, nano-ceramic material dispersion slurry, composite UV absorber component and modified halloysite powder, melt-blending them, and then extruding and granulating them through a twin-screw extruder to obtain a PET functional masterbatch; S2. Biaxially stretching the PET functional masterbatch into a film to obtain a building glass ceramic gel thermal insulation film.
10. The architectural glass ceramic gel thermal insulation film according to claim 1, characterized in that: The process parameters of biaxial stretching in S2 include: temperature of 105-115°C, stretching rate of 90-120 mm / s, and transverse and longitudinal stretching ratio of 3-4.
Citation Information
Patent Citations
Reflection-type nano ceramic-based heat insulation film and film preparation process thereof
CN114836071A
Cited By
Antibacterial antifouling ceramic material and preparation method thereof
CN121135148A